Event Detection in Twitter Using Mentioning Practice of the User (International Journal of Engineering and Computer Science, 2015)
Twitter is one of the most popular Online Social Networks (OSN’s) nowadays. Twitter is valuable source of timely information. Detecting events in the twitter is difficult task; information on Twitter is overwhelmed by huge volume of uninteresting tweets. Prior works may not be appropriate, because it focuses on only textual contents. In Twitter user may also inserts non- textual contents of their interest. Event detection in Twitter Using mentioning practice of the user (EDT), a novel method that gives desired result of creation frequency of dynamic links (i.e. mentions) that users inserts in tweets to detect important events and find the impactful words of the events The experiments we conducted shows that the proposed method can efficiently detect accurate (95%) and meaningful events.